Differences in lower extremity muscular responses between successful and failed balance recovery after slips - Lew, Fui Ling (2013)
The main purpose of this study was to examine the differences in lower extremity muscular responses between successful and failed balance recovery after slips, and across different muscle groups. Twenty-five young healthy participants were recruited who were instructed to walk on a linear walkway, and slips were induced unexpectedly during walking. Four lower extremity muscle groups in both legs were examined here, including the tibialis anterior, medial gastrocnemius, rectus femoris, and medial hamstring. Lower extremity muscular responses were quantified by muscular activation latency, muscular peak amplitude, time-to-peak, and co-contraction index. The results showed that successful balance recovery was associated with smaller muscular peak amplitude and smaller time-to-peak in the rectus femoris of the perturbed leg compared to failed balance recovery. In addition, it was also found that the muscular activation latency in the medial hamstring of the perturbed leg was significantly smaller than those in the tibialis anterior, rectus femoris, and medial hamstring of the unperturbed leg. These findings can aid in better understanding fall mechanisms due to slips and be used to establish guidelines for developing fall prevention strategies in the workplace.